Magnetic resonance spin–spin relaxation time estimation in a rat model of fatty liver disease. Issue 2 (22nd June 2017) - Alghamdi, Sami; Sinclair, Benjamin; Cowin, Gary; Brereton, Ian; Tesiram, Yasvir A.
Abstract : Purpose: To compare mono‐ and bi‐exponential relaxation model equations to discriminate between normal and fatty liver disease. Materials and Methods: Six rats on a choline deficient amino acid modified (CDAA) diet and six on normal chow were studied. Multiple spin echo images with increasing echo times (TEs) were collected at 9.4T. Pixel‐wise T2 maps were generated using mono‐exponential decay function to calculate T2M, and a bi‐exponential to calculate, short T2 component (T2S ), long T2 component (T2L ), and fractions of these components ( ρ S, ρ L ), respectively. Statistical F‐tests and Akaike's information criterion (AIC) were used to assess the relative performance of the two models. Results: F‐test and AIC showed that in the CDAA group, T2 bi‐exponential model described the signal of T2 weighted imaging of the liver better than the mono‐exponential model. Controls were best described by the mono‐exponential model. Mean values for T2M, T2L, T2S, ρ S, ρ L were 31.2 ± 0.7 ms, 72.8 ± 3.3 ms, 8.2 ± 0.6 ms, 71.2 ± 2.1%, 30.4 ± 1.3%, respectively, in CDAA rats, compared with 18.8 ± 0.5 ms, 32.3 ± 0.7 ms, 9.2 ± 1.8 ms, 79 ± 2%, 21.0 ± 1.1% in controls. Conclusion: In the fatty liver of CDAA rats we have shown that T2 weighted images fit the bi‐exponential model better than mono‐exponential decays thus providing a better description of the data. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:468–476.